A simulation study of protons heated by left/right-handed Alfvén waves generated by electromagnetic proton–proton instability. (12th October 2021) - YAO 姚, Jiansheng 建生; ZHAO 赵, Yingkui 英奎; YE 叶, Difa 地发; LI 李, Yi 毅; CHAI 柴, Lihui 立晖; SUN 孙, Jicheng 继承
Abstract: Most protons in the solar wind belong to one of two different populations, the less dense beam protons and the denser core protons. The beam protons, with a velocity of (1–2) V A ( V A is the local Alfvén speed), always drift relative to the core protons; this kind of distribution is unstable and stimulates several kinds of wave mode. In this study, using a 2D hybrid simulation model, we find that the original right-handed elliptically polarized Alfvén waves become linearly polarized, and eventually become right-handed and circularly polarized. Given that linearly polarized waves are a superposition of left-handed and right-handed waves, cyclotron resonance in the right-handed/left-handed component heats beam/core protons perpendicularly. The resonance between beam protons and right-handed polarized waves is stronger when the beam relative density is lower, resulting in more dramatic perpendicular heating of beam protons, whereas the situation is reversed when the beam relative density is larger.